2006
DOI: 10.1111/j.2042-3306.2006.tb05602.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic pharyngeal collapse in racehorses

Abstract: This study provides a classification system for dynamic pharyngeal collapse and suggests that older racehorses (> or = 4 years of age) diagnosed with PC and all horses with grade 3 PC have a poor prognosis for return to previous level of performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 10 publications
1
42
0
1
Order By: Relevance
“…Nasopharyngeal collapse, which was identified in 14.0% of horses in this study (Figure 8), has been observed during DOE examinations to be a cause of respiratory noise and/or exercise intolerance in performance horses and racehorses (Boyle et al 2006;Dart et al 2001;Kannegeiter & Dore 1995;Martin et al 2000;Strand & Staempfli 1993). Studies have found NPC to occur with considerably less frequency than other dynamic abnormalities of the URT, with a prevalence of 1.3% -18.0% in racehorses examined because of respiratory noise and/or poor performance (Kannegeiter & Dore 1995;Lane et al 2006;Tan et al 2005).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Nasopharyngeal collapse, which was identified in 14.0% of horses in this study (Figure 8), has been observed during DOE examinations to be a cause of respiratory noise and/or exercise intolerance in performance horses and racehorses (Boyle et al 2006;Dart et al 2001;Kannegeiter & Dore 1995;Martin et al 2000;Strand & Staempfli 1993). Studies have found NPC to occur with considerably less frequency than other dynamic abnormalities of the URT, with a prevalence of 1.3% -18.0% in racehorses examined because of respiratory noise and/or poor performance (Kannegeiter & Dore 1995;Lane et al 2006;Tan et al 2005).…”
Section: Discussionmentioning
confidence: 57%
“…It allowed detection of conditions that are not apparent during resting examinations such as palatal instability (PI) (Lane et al 2006), intermittent DDSP (Barakzai & Dixon 2011;Desmaizieres et al 2009;Lane et al 2006;Pollock et al 2009), left corniculate process collapse (LCPC) (Barakzai & Dixon 2011), axial deviation of aryepiglottic folds (ADAF) (King et al 2001), vocal cord collapse (VCC) (Barakzai & Dixon 2011) and nasopharyngeal collapse (NPC) (Boyle et al 2006;Strand & Staempfli 1993). In addition, it provided more information about arytenoid function at exercise (Barakzai & Dixon 2011;Desmaizieres et al 2009;Franklin 2008;Pollock et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…At that, grades B of submaximal abduction and C of dynamic collapse were further divided into three subgrades respectively. Axial deviation of the aryepiglottic fold (ADAF) was defined according to King et al 2001 and dynamic pharyngeal collapse (PC) according to Boyle et al 2006. Occurrence of a dorsal displacement of the soft palate (DDSP) was classified into rarely short (<3×/10 sec), often short (>3×/10 sec) and long to continuous (>8 sec) DDSP.…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic pharyngeal collapse may lead to partial-to-complete obstruction of the airway rostral to the glottis and marked transient increases in negative pressure with each inspiration [75]. Characterised by ventral displacement of the dorsal pharyngeal wall and/or axial displacement of the lateral walls of the pharynx, the obstruction increases in severity as the number of walls involved rises from one to three, and finally to four if PI/DDSP also occurs [75].…”
Section: Some Key Attributes Of Breathing-related Functions In Thementioning
confidence: 99%